Learning Hygiene: Mortality Patterns by Religion in the Don Army Territory (Southern Russia), 1867-1916. - Bonneuil, Noël; Fursa, Elena (Journal of Interdisciplinary History)
The article examines the mortality patterns by religion in the Don Army Territory in Southern Russia from 1867 to 1916. The factors that affected hygiene and response to epidemics are discussed as well as the relationship between mortality and religion. Also discussed are the time series of period life expectancy, the issues influencing mortality patterns by denominations, and infant and child mortality.